HPC cement materials prepared by mixing under reduced pressure. Issue 1 (January 2021) - Vojtisek, J; Novotny, R; Bartonickova, E; Hruby, P; Marko, M; Janca, M
Abstract: This article deals with HPC (High Performance composite) materials whose main advantages are increased mechanical properties, durability and stability. The limiting parameter for such materials is the presence of air bubbles that cannot be removed just by the compacting. Mixing of cement mixtures under reduced pressure can be used to reduce porosity and eliminate the presence of air bubbles. Moreover, it is associated by the improvement of the mechanical properties. The influence of preparation of HPC by mixing under the atmospheric pressure and by mixing under reduced pressure to parameters like mechanical properties, porosity, microstructure was studied in this paper. The porosity of the samples was analysed in a cross-section using an optical method. The effect of the reduced pressure on the resulting strength of the samples was observed.